Exploring the Sikh Tradition A Conversation with Eleanor Nesbitt. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Eleanor Nesbitt who is Professor Emeritus of Education Studies at University of Warwick and a poet. Eleanor Nesbitt is an expert on Hindu and Sikh culture and her interdisciplinary approach straddles religious studies, educational theory, ethnography and poetry. After inspiring insights about the time Eleanor Nesbitt spent in India and her academic path, this wide-ranging conversation provides a detailed exploration of the Sikh tradition: the history, religious tenets, other people's misconceptions about it and mor.